2020
DOI: 10.3847/1538-4357/abb377
|View full text |Cite
|
Sign up to set email alerts
|

The Cepheid Distance to the Seyfert 1 Galaxy NGC 4151

Abstract: We derive a distance of 15.8 ± 0.4 Mpc to the archetypal Seyfert 1 galaxy NGC 4151 based on the near-infrared Cepheid period–luminosity relation and new Hubble Space Telescope multiband imaging. This distance determination, based on measurements of 35 long-period (P > 25 days) Cepheids, will support the absolute calibration of the supermassive black hole mass in this system, as well as studies of the dynamics of the feedback or feeding of its active galactic nucleus.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Onken et al (2014) found M BH = (3.76 ± 1.15) × 10 7 M but assumed a distance of D = 13.9 Mpc. When adjusted for the recently published Cepheid distance to NGC 4151 of D = 15.8 ± 0.4 Mpc (Yuan et al 2020), their best-fit mass becomes M BH = (4.27±1.31)× 10 7 M . Our range of M BH values is somewhat lower, which may be attributed to a somewhat lower velocity dispersion σ in the central parts inferred from our reanalysis of the observational data.…”
Section: Comparison With Previous Resultsmentioning
confidence: 98%
“…Onken et al (2014) found M BH = (3.76 ± 1.15) × 10 7 M but assumed a distance of D = 13.9 Mpc. When adjusted for the recently published Cepheid distance to NGC 4151 of D = 15.8 ± 0.4 Mpc (Yuan et al 2020), their best-fit mass becomes M BH = (4.27±1.31)× 10 7 M . Our range of M BH values is somewhat lower, which may be attributed to a somewhat lower velocity dispersion σ in the central parts inferred from our reanalysis of the observational data.…”
Section: Comparison With Previous Resultsmentioning
confidence: 98%
“…The calculations for M BARY are detailed in Paper I, M DYN and M DM are described in Sec. 6. which found 15.8 ± 0.4 Mpc (Yuan et al 2020b). Almost all of the TF studies underpredict the distance, which seems to be caused by the adoption of an axis ratio of 0.6 when constraining the galaxy inclination.…”
Section: Notes On Individual Objectsmentioning
confidence: 93%
“…Cepheids measurement (Yuan et al 2020a), 5. Cepheids measurement (Yuan et al 2020b), 6. Cepheids measurement (Bentz et al 2019), 7.…”
Section: Notes On Individual Objectsmentioning
confidence: 99%
“…A new search of possible ULPs not classified as ULPs, but present in CC samples was carried out. Ten new candidates were found: two ULPs in M33, Pellerin and Macri [22], five new ULPs in M31 Kodric et al [23], one ULP in Yuan et al [24] and one in Bentz et al [25] (gP1, rP1 and iP1 ULP mean magnitudes obtained by Kodric et al [23] and WFC3 magnitudes by Yuan et al [24] and Bentz et al [25] were converted in the Johnson V and I magnitudes adopting transformation by Tonry et al [26] and Harris [27], respectively). In particular, the five new ULPs in M31 were identified in the framework of the Pandromeda survey [23], with a minimum period of 79.35 d. In the Kodric et al [23] sample are also included the bf two M31 variables by Ngeow et al [18], but 8-1498 (with period longer than 80 days) is listed as unclassified.…”
Section: Literature Samplesmentioning
confidence: 99%
“…The metal abundances of the all M31 ULPs are obtained from their position [19,23,32], taking into account the metallicity gradient of this galaxy derived in the framework of the PHAT survey [33]. Distances for NGC 4151 and NGC 6814 are those derived by Yuan et al [24] and Bentz et al [25], respectively. For NGC 4151, in the literature, there is no reliable metallicity determination, whereas NGC 6814 has approximately a solar average abundance [34].…”
Section: Literature Samplesmentioning
confidence: 99%